Development of an Efficient, High Purity Continuous Flow Synthesis of Diazepam - Nicholas, Robert J.; McGuire, Michael A.; Hyun, Seok-Hee; Cullison, Madeline N.; Thompson, David H. (Frontiers in Chemical Engineering, 2022)
In an effort to strengthen the resiliency of supply chains for active pharmaceutical ingredients (API), continuous manufacturing (CM) processes may be optimized with respect to improved chemoselectivity, production rate, yield, and/or process intensity. We report an optimized two-step continuous flow synthesis of diazepam, an agent on the World Health Organization’s (WHO) list of essential medicines. Different conditions were rapidly screened in microfluidic chip reactors by varying residence times, temperatures, solvents, and ammonia sources to identify the best telescoped reaction conditions. We report a telescoped flow synthesis that uses two microreactors in series, set to 0 °C and 60 °C, respectively, to produce a 96% yield of 91% pure diazepam within 15 min using an NH4Br/NH4OH solution in the second step. Diazepam of >98% purity was obtained after a single recrystallization.